An Experimental Study on the Exit Location on the Evacuation Efficiency under High Competition Condition. (2018) - Wu, Fan-yu; Wang, Guo-yuan; Si, You-liang; Lin, Peng
Abstract: Crowd dynamic has attracted the interest of scientists as a number of crowd incidents happened in the last decades. A series of mice evacuation experiments were conducted in a test container with the size of 1.5 m long and 0.3 m wide. A 2 cm-wide exit is placed at the middle of two side walls respectively, i.e., one on the 1.5 m wall and the other on the 0.3m wall. The mice were trained to pass through the exit. Joss sticks were used to produce smoke with concentration high enough to drive the mice to escape under high competition. The evacuation process was video-recorded for further analysis. The average escape time of mice is around 279s when the exit is set on the 1.5m wall, whilst the average escape time is 335s when the exit is set on the 0.3m wall. The relocation of exit from the 0.3 m wall to the 1.5 m wall significantly reduced the average evacuation time by around 16.7%.